mHealth Apps for Promoting Diabetes Self-Management Behaviors: A Mini-Review of Recent High-Quality Systematic Reviews - Muhammad Thesa Ghozali (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Mobile health (mHealth) applications have emerged as promising tools to support diabetes self-management, yet their overall effectiveness remains to be systematically evaluated. Objective: This review evaluates the effectiveness of mobile health (mHealth) apps in promoting diabetes self-management behaviors by synthesizing findings from high-quality systematic reviews published in the last five years. Method: A comprehensive search was conducted across Scopus, PubMed, Cochrane Library, EBSCO Host, and ProQuest. Six systematic reviews met the inclusion criteria, with a mean AMSTAR quality score of 10.33 out of 11. Reviews were analyzed for clinical outcomes, user engagement, and adherence. Result: Findings indicate that mHealth apps significantly improve glycemic control, evidenced by reductions in HbA1c levels. Additional benefits include increased user engagement, better adherence, behavioral improvements, and psychosocial outcomes such as reduced anxiety and improved quality of life. However, heterogeneity across studies, challenges related to digital literacy, and concerns about data privacy limit generalizability. Conclusion: mHealth apps show strong potential to enhance diabetes self-management through clinical and psychosocial benefits. Future work must address barriers such as digital literacy, data security, and variability in intervention quality to support sustained adoption and effectiveness.